2014
DOI: 10.3390/ijms15034565
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Plant Cell Elongation: A Role for Acetylcholine

Abstract: We investigated the effect of auxin and acetylcholine on the expression of the tomato expansin gene LeEXPA2, a specific expansin gene expressed in elongating tomato hypocotyl segments. Since auxin interferes with clathrin-mediated endocytosis, in order to regulate cellular and developmental responses we produced protoplasts from tomato elongating hypocotyls and followed the endocytotic marker, FM4-64, internalization in response to treatments. Tomato protoplasts were observed during auxin and acetylcholine tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 111 publications
(142 reference statements)
1
23
0
Order By: Relevance
“…Acetylcholine is a small neurotransmitter molecule, reportedly involved in regulation of growth and development by modulating a multitude of physio‐biochemical processes in plants and animals (Tretyn & Kendrick ; Sansebastiano et al . ). However, little evidence is available in the literature on the function of ACh in plant adaptation to salinity stress.…”
Section: Discussionmentioning
confidence: 97%
“…Acetylcholine is a small neurotransmitter molecule, reportedly involved in regulation of growth and development by modulating a multitude of physio‐biochemical processes in plants and animals (Tretyn & Kendrick ; Sansebastiano et al . ). However, little evidence is available in the literature on the function of ACh in plant adaptation to salinity stress.…”
Section: Discussionmentioning
confidence: 97%
“…The drug BFA is often used to demonstrate the involvement of Golgi in vacuolar trafficking (for a review see [36]) but it is also acting on endosomal compartments and on recycling to the plasmalemma, causing the formation of BFA bodies [37]. Recent results in Nicotiana [17], indirectly confirmed in tomato [38], indeed suggest that GFPChi transits via an intermediate compartment independent from the trans -Golgi Network (TGN) but involved in the late events of BFA bodies formation.…”
Section: Chitinase Sorting a Hidden Pathmentioning
confidence: 99%
“…Because rooting (in vivo or in vitro) is mainly affected by auxin, the effectiveness of Ach in promoting root grown Table 1 Percentage of germinated (%G), germination speed index (GSI), first count (%FC), strong normal seedlings (SNS), weak normal soybean seedlings (WNS), length shoot (LS), length root (LR), length total (LT), dry matter of shoot (DMS), root dry mass (RDM), total dry matter (DMT) and relationship between root and shoot (R/S) soy genotype Intacta, subjected to different concentrations of acetylcholine and different osmotic conditions suggests an interesting possibility on the mechanism of action of Ach and its involvement with auxin (Baluska et al 2005). Some experiments have shown that Ach combined with auxin increases the expression of the expansin LeEXPA2 gene in the hypocotyls of tomatoes, when compared to auxin and Ach treatments separately (Di-Sansebastiano et al 2014). Expansins are known to be involved in cell elongation, being codified by a multigene family, where LeEXPA2 is included, which are regulated by auxin in the growing regions of young tomato hypocotyl (Caderas et al 2000).…”
Section: Discussionmentioning
confidence: 99%